Reine Vermögensschäden im Europäischen Internationalen Deliktsrecht : Zuständigkeit und anwendbares Recht - Meyle, Hannes (Duncker & Humblot GmbH, 2021)
Illegal actions that lead to pure financial losses pose a particular challenge in cross-border disputes. The special tortious place of jurisdiction requires that the damaging event can be localized. However, more recent judgments by the European Court of Justice show that determining the scene of a crime is becoming increasingly problematic in the case of property crime. Comparable difficulties arise when determining the applicable law. Based on a practice-oriented investigation of various case groups, the work addresses the question of whether the crime scene rule is at all suitable for localizing property crimes. The main finding is that the crime scene rule regularly fails in the case of property offenses and does not guarantee legal certainty either in jurisdiction law or in coordination law. Depending on the type of offence, it is advisable to restrict the crime scene rule or to orientate yourself towards the affected market. Building on this, the work contains concrete reform proposals for the Brussels I-VO and the Rome II-VO. »Pure Economic Loss in European Private International Law. Jurisdiction and Applicable Law" In private international law, localization of cross-border torts that result in pure economic loss is unpredictable. Both jurisdiction and applicable law are dominated by case-by-case decisions. The problem already existed at the time of the German Reichsgericht and it has not been solved by the ECJ yet. The thesis shows why the place of damage is an unsuitable connecting factor for pure economic loss cases and develops reform proposals.